CELLULOSE-SILICA COMPOSITES OF HYDROPHILIC- HYDROPHOBIC NATURE - Egamberdiev , Elmurod Abduqodirovich; Muratkulov , Olimjon Komiljonovich; Shomurodov, Dostonbek Qurbonsho o‘g‘li; Sobitov , Obidjon Sadriddin o‘g‘li (Innovative Development in Educational Activities, 2023)
It is known that the study of the properties of cellulose-silica composites has attracted great interest in recent years. Because of this, cellulose- silica composites have their own characteristics. That is why it is important to obtain composite materials based on it at present. In the thesis, cellulose-silica composites were synthesized, their structure, physico-chemical properties were studied. As a result of the conducted studies, various thermodynamic properties, including the average energy of mixing Agm, Gibbs energy AGi, capillary-pore indicators, and the limit of true adsorption were determined. Based on water vapor sorption properties of water-soluble cellulose-silica composites obtained in different proportions, their capillary-pore structures (capacity of monolayers, specific surface area, and total volume of pores and radius of pores) were calculated. The hydrodynamic properties of aqueous solutions of the samples under different conditions were studied.